ROLE OF THE HEAD OF SCHOOL AS A MANAGER IN IMPROVING THE QUALITY OF ISLAMIC RELIGIOUS EDUCATION IN MA FATHUL HUDA SIDOREJO SAYUNG DEMAK - Aydi, Ulil (Universitas Islam Negeri Alauddin Makassar, 2018)
There are 2 main problems in this research, namely, first, the role of the head of school as a promoter in improving the quality of Islamic education with the function, second, the role of the head of school as a promoter in improving the quality of Islamic education with function. This research was conducted at MA Fathul Huda Sidorejo Sayung Demak. This type of research is field research using descriptive qualitative analysis research method, namely the researcher observes and interacts with the head of school, teachers, employees and students in MA Fathul Huda Sidoejo Sayung Demak with interviews and observations and reviews the documentation. The results of this study indicate that the role of the head of school as a manager in improving the quality of Islamic Education with administrative functions that include planning, organization, implementation and supervision can work well based on theoretical basis. The role of the head of school as manager in improving the quality of Islamic Religious Education with an operative function focused on their respective fields such as administration, library, laboratory and student affairs. From the fields already mentioned, there are several fields that are in accordance with the theoretical basis and there are also obstacles or obstacles in its implementation, including: not all employees and teachers master the work in accordance with their fields, lack of teaching staff, facilities and infrastructure.